The shifting landscape of private healthcare providers before and during the COVID-19 pandemic: Lessons to strengthen the private sectors engagement for future pandemic and tuberculosis care - Widarna, Rodiah; Afifah, Nur; Djunaedy, Hanif Ahmad Kautsar; Sassi, Angelina; Vasquez, Nathaly Aguilera; Oga-Omenka, Charity; Salindri, Argita Dyah; Lestari, Bony Wiem; Pai, Madhukar; Alisjahbana, Bachti (Public Library of Science (PLOS), 2024)
Introduction COVID-19 pandemic changed many aspects of healthcare services and deliveries, including among private healthcare providers (i.e. private healthcare facilities [HCFs] and private practitioners [PPs]). We aimed to compare the spatial distribution of private providers and describe changes in characteristics and services offered during and before the COVID-19 pandemic, and explore the tuberculosis (TB) and COVID-19 related services offered by the private sector in Bandung, Indonesia. Methods A cross-sectional study with historical comparison was conducted in 36 randomly selected community health centers areas (locally referred to as Puskesmas) in Bandung, Indonesia, during the COVID-19 pandemic from 5th April 2021 – 27th December 2021. Data pertaining to before the COVID-19 pandemic was abstracted from a similar survey conducted in 2017 (i.e., INSTEP study). We obtained latitude and longitude coordinates of private healthcare providers and then compared the geographical spread with data collected for INSTEP study. We also compared characteristics of, and services provided by private healthcare providers interviewed during the COVID-19 pandemic with those previously interviewed for INSTEP study. Differences were summarized using descriptive and bivariate analyses. Results From April–December 2021, we surveyed 367 private HCFs and interviewed 637 PPs. Compared to INSTEP study data, the number of operating HCFs was reduced by 3% during the COVID-19 pandemic (401 vs. 412 before COVID-19), although we observed increases in laboratory service (37.8% increase), x-ray service (66.7% increase), and pharmacy (18.1% increase). Among a subset of private HCFs managing patients with respiratory tract infection symptoms, a quarter (60/235, 25.3%) indicated that they had to close their facilities in response to the emerging situation during the COVID-19 pandemic. For PPs, the number of practicing PPs was reduced by 7% during the COVID-19 pandemic (872 vs. 936 before COVID-19). Interestingly, the number of practicing PPs encountering patients with TB disease increased during the COVID-19 pandemic (42.9% vs. 35.7% before COVID-19, p = 0.008). Conclusion This study confirmed that the COVID-19 pandemic adversely impacted health care service deliveries in private sectors, largely marked by closures and shortened business hours. However, the increased service capacities (laboratory and pharmacy), as well as significant increase in the number of patients cared for TB disease by PPs during the COVID-19 pandemic, made a more compelling case to further the implementation of public-private mix model for TB care in Indonesia.
© 2024 Widarna et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Keywords: COVID 19; pandemics; health care facilities; tuberculosis; health care providers; Indonesia; tuberculosis diagnosis and management; virus testing